Giardiasis in cattle: clinical assessment of giardia lamblia in cattle at Basrah, Iraq - Al-Saad, Rasha; Al-Emarah, Ghazi (International Journal of Scientific World, 2014)
The aim of this study is for assessment cattle giardiasis clinically. It is first time study in type done in Iraq. It was conducted from September 2012 until May 2013 throughout it collected 1049 fecal samples from cattle of various ages and of both sexes, collected randomly from different areas of the northern Basrah. About 322 positive cases have been recorded in cattle and the infection rate was 30.6%. 241 cases out of 322 showed clinical signs while 81 infected cows did not show clinical signs which are asymptomatic. The clinical examination data showed variety of presentation among symptoms and signs. The percent of symptomatic type was higher than the percentage of asymptomatic giardiasis in cattle. The study reported symptoms such as diarrhea, foul smelling stool, and flatulence, loss of appetite, elevated temperature, constipation and emaciation in different proportions. Keywords: Giardia, Diarrhea, Asymptomatic, Cattle.